A new species of duck from central colombia (1946)
For a number of years there has been persistent report of "black ducks" from the mountain lakes of central Colombia, with the supposition on the part of hunters that these were the well-known species of that name of eastern North America. The senior author made some inquiry into the matter especially following a note published in CALDASIA N,o.9, Jan. 6, 1944, p. 407, where Mr. F. C. Lehmann gave a brief summary of what was known of these birds. His account indicates that dark-colored ducks are of common occurrence in various part of Colombia, especially in the Bogotá Savanna where they are called "pico de oro" or "picodioro". He recorded others near Cali in the Cauca Valley where they are known as "pato amarillo". The matter is of especial interest since the black duck of North America, Anas rubripes, while migratory in the northern part of its range is not known to pass south of the southern United states except for two or three casual records from the West Indies. Shortly before this, on September 17, 1943, Brother Nicéforo Maria of the Instituto de La Salle in Bogotá wrote that he has forwarding to the U. S. National Museum as a gift a small collection of birds taken principally by himself for which he desired identifications. When these arrived in due time there was among them a strange duck somewhat resembling Anas spinicauda, but differing in form and especially in much darker color. There was some supposition that it might be a hybrid, but this seemed hardly probable, so that the question of the "black ducks" reported from this area came immediately to mind.